Playing “hide and seek” with Texas tortoises: value of a detector dog - Moeller, Christin; Perales, Saren; Rodriguez, Wraith; Henke, Scott E.; Rideout-Hanzak, Sandra; Eversole, Cord B. (Frontiers in Amphibian and Reptile Science, 2024)
Texas tortoises (Gopherus berlandieri) were once considered common and abundant throughout southern Texas with densities as high as 16 tortoises per hectare. Today, density estimates are 0.25 tortoises per hectare, which constitutes about a 98% population decline. Because of their low numbers and elusive behavior, Texas tortoises can be difficult to find. We demonstrate the value of using a detector dog as a time saving method in locating Texas tortoises. We glued VHF radio transmitters onto 9 adult tortoises and released them in a 5-ha plowed and short-grass pasture that contained mesquite (Prosopsis glandulosa) mottes, habitat conducive for Texas tortoise habitat selection. We calculated the Detectability Index (DI) as the detection rate (# tortoises found/minute) × percent tortoises from the known population found within 60 minutes.We compared DIs via telemetry, detector dog, and 'cold' (no equipment or knowledge) human searches. We used the time required to find all tortoises when a searcher had knowledge of locations as the baseline. Our baseline DI was 0.79, followed by telemetry (0.13) and detector dogs (0.11), while 'cold' searches was 0.02. Telemetry, detector dog, and cold searches were 6fold, 7-fold, and nearly 40-fold slower, respectively, than having knowledge of tortoise locations.However, the combination of using detector dogs with telemetry resulted in a 50% time savings than single methods. Telemetry was useful in locating a generalized area with a tortoise but a detector dog was 2X faster in visually locating the tortoise once the area was identified.Therefore, we recommend the use of detector dogs as a time-saving method when conducting research on Texas tortoises.